Geochemical Tracer in Coral as a Sea Surface Temperature Proxy: Records from Jukung Coral - Cahyarini, S. Y.; Zinke, J. (ITB Journal Publisher, LPPM ITB, 2010)
Sr/Ca has been analyzed from coral core from the Seribu Islands reef complex i.e Jukung Island. SST from ERSST dataset and air temperature measured at Jakarta is used for Sr/Ca calibration. The results show that Jukung Island coral Sr/Ca correlates better with SST than with air temperature. A comparison between the Sr/Ca records with the Nino 3.4 index shows that Jukung coral sites indicate warming sea surface temperatures during the beginning of El Nino events followed by cooling temperatures at the end of El Nino years.